Un siècle de Mouvement wallon 1890-1997 - Dupuis, Patrick; Humblet, Jean-Emile; Collignon, Robert (Gerpinnes : Editions Quorum, 1998)
Bibliotheek François Vercammen
Frans
Monografie
Keywords: Waalse Beweging